Urbanization trends and groundwater issues in Asian cities - Neethu Vijaya,; Shaharudin Idrus,; Mazlin Mokhtar,; Nimisha Krishnankutty, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Above half of the global population resides in urban areas and the increasing population is highly dependent on groundwater for its drinking water and agricultural requirements. Asia and Africa are urbanizing at a higher rate than other developed regions. Asia contributes to 53 percent of global urban population and is expected to reach 55 percent by 2025. This article seeks to explore the urbanization trends in Asia and its impacts on groundwater resources through evaluating five countries- China, India, Indonesia, Japan and Malaysia. China and India are two major contributors of world’s urban population; Indonesia, Japan and Malaysia are other three rapidly urbanizing countries in Asia. The analyses are drawn based on a critical review of previous studies conducted on the topic in Asia. The study has found that most populous mega-urban regions in the world and in Asia are located in these five countries. The urban growth rate of China is double or little less than India, Indonesia and Malaysia; Japan is expected to exhibit a declination in its urban population while continue to maintain a high urbanization level during 2014-2050. Urbanization in Asia is not environmentally sustainable and it puts huge pressure on groundwater resources, degrading its quality and quantity, raising concern for resultant land subsidence. India poses a higher pressure on its groundwater resources, followed by China, Indonesia, Japan and Malaysia. Innovative technological and governance solutions with given priority on infrastructural development and environmental conservation is required to tackle urbanization dilemma existing in Asia.